Pengaruh Investasi China terhadap Pertumbuhan Ekonomi Indonesia dengan Uji Kausalitas Granger - Siregar, Petrus; Imangingsih, Niniek (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
The purpose of this research is to inform about the influence of Chinese investment on Indonesia's economic growth. The data sample taken is a secondary time series data type with a time range from 2006 to 2021 sourced from BKPM and BPS. The data analysis used Granger causality through the use of Eviews 13. The results of the hypothesis test explained that there was no significant and positive impact from the causality relationship between the investment value variable and the economic growth variable but on the contrary had a positive but not significant causal relationship between the economic growth variable and the economic growth variable. investment value.